Analysis of gender representation on transfusion medicine journal editorial boards: Comparison between 2019 and 2022. Issue 1 (25th October 2022) - Jacobs, Jeremy W.; Adkins, Brian D.; Woo, Jennifer S.; Lally, Kimberly; Booth, Garrett S.
Abstract: Background and Objectives: A 2019 study highlighted significant gender inequities among blood banking and transfusion medicine (BBTM) journal editorial boards. We sought to assess if the representation of women has improved in the intervening 3 years. Materials and Methods: We analysed the gender composition of nine BBTM journal editorial boards as of 13 September 2022, including the seven journals studied in 2019. We compared this to the proportion of females (term used by authors) on seven BBTM journal editorial boards in 2019 to assess change in the editorial board composition. We also assessed gender composition by editorial position (editor‐in‐chief [EIC], associate/assistant/titled editors and editorial board members). Results: Nine BBTM journals have a total of 398 editorial positions and comprise significantly more men than women (68.8%, 274/398 vs. 31.2%, 124/398; p < 0.001). Among the seven journals analysed in 2019, the proportion of women on these seven editorial boards has remained unchanged (2019: 30.1%, 81/269 vs. 2022: 31.9%, 103/323; p = 0.66) despite the addition of 54 editorial positions. Conclusion: Women remain inequitably represented on journal editorial boards among all journal editorial positions. Although advocacy efforts are increasing, there has been limited improvement in gender equity in 3 years, despite a 20% increase in editorial positions.